ECONOMIC LIFE IN UZBEKISTAN IN THE 60-80S OF THE 20TH CENTURY (World Bulletin of Social Sciences, 2023)
This article, based on historical literature and archival materials, highlights the work done by the Soviet state in the second half of the twentieth century in the field of economic policy. The issues of the influence of economic policy on the social life of the population are also disclosed